The evaluation of public health in South Eastern Europe: from transition to progress (Italian Journal of Public Health, 2009)
Background: The public health services project of the South-eastern Europe health network has undertaken an evaluation of public health services in its nine member countries. The purpose of the evaluation of public health services provision in the South-eastern European (SEE) countries is to understand where these countries now stand in public health, the institutional, organisational, legislative and service delivery developments that are taking place and to identify strengths and weaknesses in their public health systems and services in order to inform decision making about investment and future reform.Methods: The evaluation was orientated around “essential public health operations” that are deemed to form the core of public health activities and services and to be indispensable to the delivery of modern public health services in any country. The evaluation analysed these activities and services within the structure of the health system functions of stewardship, resource generation, financing and service delivery, as developed by WHO.Results: The results demonstrate a mixed picture of strengths and weaknesses within the context of significant social, economic and political challenges in the region. Among the many visible and significant strengths in public health services in the region are well developed networks of public health institutes with well defined surveillance systems, highly experienced and well educated public health professionals as well as many positive examples of service delivery. But there are also many concerns and challenges, not the least of which is political focus, direction and support for modern public health services, as well as funding. Collaboration and partnership among sectors is weak and information and communication systems are inadequate and not sufficiently integrated.Conclusions: Having emphasized the main weak and challengeable points in the Public Health systems and services in the SEE countries, the evaluation is also a first step to defining a way forward in the SEE countries to ensure that the turmoil of ‘transition’ is only a prelude to the comprehensive modernisation of public health services.
Keywords: South East Europe; Public Health Services; Future Challenges